DESCRIPTION OF THE KIDNEY OF BROILER CHICKEN INFUSED BY FLOOD INFUSION AFTER EXPERIENCING TRANSPORT STRESS - Amiruddin, Muh; Suwiti, Ni Ketut; Arjana, Anak Agung Gde (Buletin Veteriner Udayana, 2022)
The transportation of broiler chickens can cause stress to broiler chickens resulting in a decrease in body weight and high mortality. Stress causes disturbances, causing changes in the organs that make up the chicken body, one of which is the kidneys. This study aims to determine the effect of infusion of Dadap ( Erythrina Subumbrans ) leaves as an antioxidant in broiler chickens subjected to transport stress at 33°-35°C for 4 hours. This study used a completely randomized design (CRD) with a 3x2x5 factorial pattern with three replications. The number of samples used were 30 broiler chickens which were divided into 5 treatment groups, namely P0: negative control; P1: positive control and given vitamin C 2 gram/L; P2: 1000 ppm of Dadap leaf infusion is given; P3: 2000 ppm of Dadap leaf infusion was given and P4: 3000 ppm of Dadap leaf infusion was given. In the eighth result, after being given transport stress treatment, the kidneys were taken and then histological preparations were made with Hematoxylin Eosin (HE) staining. Parameters observed were degeneration, necrosis and infiltration of inflammatory cells. Histological scoring data were then analyzed using the Kruskal-Wallis test, if there was a significant difference followed by the Mann-Whitney test. The results showed that giving dadap leaf infusion to broiler chickens that were not given stress reduced necrosis (P<0,01) while stress-treated chickens reduced necrosis (P<0,01) and inflammatory cell infiltration (P<0,05). It was concluded that the administration of 10% dadap leaf infusion with a concentration of 2000 ppm and 3000 ppm could improve the histological picture of the kidneys of broiler chickens experiencing transport stress.